Problem of People’s Sobriety in the 3rd State Duma (1907-1912) - I. A. Shevchenko (Научный диалог)
The article is devoted to the problem of developing in the Russian Empire State Duma of the 3rd convocation (1907-1912) a set of anti-alcohol measures, which mainly concerned the peasant population of the country. Special attention is paid to the activities of deputies from the peasants in this direction. Their approaches to the problem of spread of sobriety in the Russian village are analyzed. The various stages of the special Duma “Commission on measures of fight against alcoholism” is discussed, among the members of which Samara deputy, Octobrist, a native of the peasants, M. D. Chelyshov stood out. On the other hand, the reaction of the Russian peasantry to the development of the anti-alcohol bill in the Duma is analyzed. To this end, the article involves various peasant letters and petitions sent to the people’s representation or published in the periodical press. On the basis of historical sources it is concluded that the rural inhabitants in the period under review as the most effective measure to combat alcoholism saw the elimination of drinking trade. Largely for this reason, the government in 1914 established “dry law” in the country. The novelty of the study is to attract diverse sources - previously unpublished archival data, verbatim records of Duma meetings, press materials.